Pembelajaran Daring: Analisis Komunikasi Melalui Media Komputer pada Mahasiswa Ilmu Komunikasi Universitas - Hermawan Lubis, Suci Amalia; Sahputra, Dedi; Dwiana, Ressi (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
This research is motivated by the Covid-19 pandemic that affected Indonesia, leading the Ministry of Education and Culture to mandate universities to conduct remote learning activities. The study aims to understand how online learning is conducted by Communication Studies students at Medan Area University. An analysis of Computer Mediated Communication (CMC) is employed to discern the supportive and inhibiting factors for students engaged in online learning. The research methodology is qualitative, utilizing data collection techniques such as observation, interviews, and documentation, followed by data reduction, presentation, and conclusion drawing. The findings indicate that (1) there are various learning media aiding online learning. (2) Accessibility to learning media is a crucial supportive factor in online education. (3) The network frequently becomes a barrier for students undertaking online learning. (4) The dimensions of Computer Mediated Communication (CMC) align with the implementation of online learning, particularly in disseminating information through CMC, reaching a wide audience.